Factors associated with participation in a diabetes prevention program in Austria: a prospective cohort study. (September 2012) - Teuschl, Yvonne; Matz, Karl; Dachenhausen, Alexandra; Tuomilehto, Jaakko; Brainin, Michael
SUMMARY Aims: This study aims to identify factors associated with participation in and adherence to a low-intensity diabetes prevention program.Methods: A total of 644 subjects who were at an intermediate-to-high risk for developing diabetes were enrolled in this study, aiming to acheive weight reduction, diet changes and regular physical activity.Results: Attendance at the baseline medical examination (n = 198) was associated with higher diabetes risk, being more anxious, lower fat intake and being unsatisfied more often with bodyweight compared with nonattendance. Workshops were attended by 142 individuals who were older and had lower levels of low-density lipoprotein cholesterol than nonattendees. Participants at the final medical examinations (n = 80) had a higher level of education, better self-rated fitness, fewer signs of depression and lower diastolic blood pressure than nonparticipants.Conclusion: Self-perceived diabetes risk can thus motivate people to participate in a diabetes prevention program. Adherence could be improved by adapting interventions to the education, possible depressive symptoms, fitness and health of participants.